A utilização das tecnologias digitais de informação e comunicação no ensino remoto emergencial, durante o período de pandemia da COVID - 19 - SILVA, Márcio Andrei Silva da (2023)
The Coronavirus (COVID-19) pandemic caused significant changes in the daily life of contemporary society, including in the educational scenario, as a result, there was a suspension of face-to-face activities, the adoption of social distancing and the implementation of Emergency Remote Teaching. In this way, this study aims to analyze the quality of Emergency Remote Teaching through the use of Digital Information and Communication Technologies in times of a pandemic, and more, to verify the quality of the internet connection, as well as the interaction of the teacher with the student. This is an exploratory study outlined by quantitative and qualitative approaches, and is configured in a bibliographical, documental and field research. In this way, the essay is based on bibliographical studies, highlighting the main ones by Silva (2018), Lima (2021) and Cordeiro (2020) that address the object of this research. With regard to field research, this was developed with students from the Integral High School E.M.I Prof.ª Benvinda de Araújo Pontes/Abaetetuba-Pa. It was found from the data collected that students and teachers have knowledge of technologies, however, some flaws in the quality of Emergency Remote Teaching are observed, such as: lack of understanding of the content, absence of pedagogical practices that suit the online mode, poor quality of internet connection and lack of student/teacher interaction. Thus, it is concluded that from the students' reports, there is dissatisfaction with emergency remote teaching, as this modality has become insufficient to guarantee quality learning without prejudice, thus needing to be analyzed, discussed and improved.